IMPACT OF GREEN MARKETING ON CONSUMER ATTITUDE TOWARDS PURCHASING FMCG PRODUCTS - DHANASEKAR R,; Dr. A SANKAR, (Utilitas Mathematica, 2025)
The focal persistence of this investigation is to recognize how marketing mixes, especially with reference to promotion and pricing and how they can be incorporated by the organizations to guide them to consumption eco-friendly products. The primary focus is on consumer behavior and will be analyzed to understand their perception towards various components of green marketing. This research emphases on few aspects of numerous factors secondhand by concerns that has influence on the buyers’ attitude towards these products and furthermore there are a lot of categories within FMCG sector and various categories have different approach to the market, however one main aspect of it is promotion as FMCG products needs to be approaching and appealing fast to the consumers, thus all of them engage in promotional activities and the most traditional one is video advertisement and print media advertisement. The study will use a sample of minimum 200 respondents via analysis technique through a structured survey and convenience sampling technique is used. Data are evaluated using descriptive analysis and correlations. It is observed that, Executive sought to be focusing on green displays and even making them more appealing to reach consumers, as unplanned decisions play an important role for daily products particularly when customers go to the store and many items which are not on their shopping list are eventually bought.